KETERKAITAN GAYA BELAJAR VISUAL AUDITORI KINESTETIK (VAK) DENGAN MOTIVASI BELAJAR SISWA PADA MASA PANDEMI COVID 19 (SURVEI DI SMK KARYA BAHANA MANDIRI BEKASI) - Irna Kumala; Ufiya Putri Adhiyati; Rosalina Dewi Heryani (Universitas Indraprasta PGRI, 2022)
The Covid-19 period is a difficult time where the education is also one of many areas that got most impacted. The teaching and learning process now need to be changed drastically and affecting the motivation of learner. This research’s objective is to find out the effect of VAK’s (Visual Auditory Kinesthetic) learning style on students' motivation when learning in this Covid 19 pandemic. The research approach was quantitative with a survey method. The research was held at SMK Karya Bahana Mandiri, Bekasi, starting from October 2021 – January 2022, and collecting the data through observation, questionnaires, and documentation. The population was 67 students with simple random sampling technique. The outcome of simple linear regression analysis is Y = 44.48 + 0.46 X. Then, correlation of coefficient value is 0.44, it means a moderate relation between VAK learning styles and students' learning motivation happened. Value of the coefficient of determination is 19.36%, it means that Visual Auditory Kinesthetic (VAK) learning style variable contributes to learning motivation by 19.36%, while the influence of other factors is not examined. For results of the hypothesis shown that the value of tcount > ttable is 4.9497 > 1.9971, that means there is a direct effect VAK learning style on students' learning motivation in this pandemic (a survey at SMK Karya Bahana Mandiri, Bekasi). The conclusions with the test of simple regression line analysis, correlation of coefficient test, test of coefficient determination, and hypothetical test are showing same effect of VAK studying Style on Student’s Learning Motivation in this Covid 19 Pandemic